PELAKSANAAN TAX COMPLIANCE DALAM UPAYA OPTIMALISASI PENERIMAAN PAJAK DI KOTA YOGYAKARTA - Dahliana Hasan (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
The result showed that tax compliance was not internalized yet within taxpayerself either individual or corporate. This was proven by failing to fulfill the cumulative tax compliance criteria. There were some supporting factors of tax compliance such as tax socialization through radio and newspapers and a new taxpayer would be invited to follow the seminar on taxation every 25th permonth, however, there were also some obstacle factors either done by fiscus (government) or done by taxpayers which have made tax compliance could not perform well. As a consequence, the optimum tax revenue in Yogyakarta could not be reached.